Biodegradability and mechanical properties of poly-(beta-hydroxybutyrate-co-beta-hydroxyvalerate)-starch blends. - Ramsay, B A (1993)
Wheat starch granules and poly-(beta-hydroxybutyrate-co-beta-hydroxyvalerate) [P(HB-co-HV), (19.1 mol% HV)] were blended at 160 degrees C. Increasing the starch content from 0 to 50% (wt/wt) decreased the tensile strength of P(HB-co-HV) from 18 MPa to 8 MPa and diminished flexibility as Young's modulus increased from 1,525 MPa to 2,498 MPa, but overall mechanical properties of the polymer remained in a useful range. A mixed microbial culture required more than 20 days to degrade 150-microns-thick samples of 100% P(HB-co-HV), whereas samples containing 50% (wt/wt) starch disappeared in fewer than 8 days. Starch granules degraded before P(HB-co-HV) did. Aerobic degradation proceeded more rapidly than anaerobic degradation.